Pandangan Hukum Islam tentang Tradisi Tegak Tegei dalam Pembagian Kewarisan pada Masyarakat Lampung Pepadun: Studi pada Masyarakat Kelurahan Menggala Tengah, Kecamatan Menggala, Kabupaten Tulang Bawang - Ahmad Adi Jaya; Iskandar Syukur; Zikri Zikri (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study discusses the Islamic legal perspective on the Upright Tegei tradition in the distribution of inheritance in the Lampung Pepadun Menggala community. The Upright Tegei tradition is the practice of appointing the groom as the eldest child or heir in the bride's family, especially when the woman is an only child or has no brothers. This tradition is carried out before the traditional wedding procession takes place. This study aims to determine the practice of implementing the Upright Tegei tradition in the distribution of inheritance in the Lampung Pepadun Menggala community, as well as to analyze the Islamic legal perspective on this tradition. This type of research is field research with a qualitative descriptive approach. Data were obtained through observation, interviews, and documentation, with primary data sources from traditional leaders, community leaders, and related parties, and secondary data from relevant literature. The results of the study indicate that the Upright Tegei tradition is a form of custom that aims to maintain the continuity of the family's social line, customary position, and the distribution of responsibilities in the female family. In the perspective of Islamic law, this tradition can be understood as part of the ‘urf (customs/customs) that can be accepted as long as it does not conflict with the principles of sharia, especially in terms of lineage and inheritance. Therefore, the tradition of holding tegei can be accepted in Islamic law as long as it only functions as a socio-customary recognition and does not change the provisions of lineage or inheritance rights that have been established by sharia. Based on the results of the study, the tradition of holding tegei in the distribution of inheritance is based on the view of Islamic law that adopted children receive property in the form of grants. This is because adopted children are positioned as biological children who will care for the bride's parents because they are considered the first male child in the woman's family. This research was conducted to avoid doubts in the distribution of inheritance while providing economic security for adopted children in the future. However, when examined according to Islamic law, this practice is inconsistent with the principles of justice and the provisions for inheritance distribution as stipulated in Surah An-Nisa verses 7 and 11. In Islamic teachings, giving gifts to adopted children is permitted, especially after the separation of joint assets (gono-gini) as stipulated in Article 35 of Marriage Law Number 1 of 1974. However, if the giving of gifts is excessive and does not consider the rights of legitimate heirs, it is considered contrary to the principles of justice and has the potential to trigger conflict within the family.